Farm types and adoption of proven innovative practices in smallholder bean farming in Angonia district of Mozambique - Makate, C.; Makate, Marshall; Mango, N. (Emerald Group Publishing, 2018)
© 2018 Emerald Publishing Limited. Purpose: Improving the adoption rates of proven innovative practices in bean farming and their impacts on livelihoods requires persistent promotion of practices, complemented by rigorous socioeconomic analysis that recognises the diversity of smallholder farmers. The purpose of this paper is to typify farm households in Angonia district of Mozambique, based on their socioeconomic characteristics prompting the adoption of proven innovative practices in bean production, management, and marketing. Design/methodology/approach: The authors use a multivariate statistical analysis approach that combines principal component analysis, and cluster analysis to clearly identify five distinctive farm household types with respect to the adoption of proven innovative practices in smallholder bean farming using socio-economic factors. Findings: The study findings show that various socioeconomic factors define clusters and can be associated with the adoption and use of innovative practices in smallholder bean farming. The five farm types identified are: female landowners with small farm sizes (29.52 per cent); educated farmers with access to credit (6.63 per cent); relatively rich male land owners with large farm sizes and low education (8.73 per cent); youthful, inexperienced and poor male farmers (6.33 per cent); and experienced female farmers with high labour endowments (8.43 per cent). The respective farm types seemed to have different patterns in the adoption of proven innovative practices in bean farming. Originality/value: The authors recommend that policy makers promote strategies meant to raise adoption of innovative practices in bean production, management and marketing in Mozambique that takes into account household diversity. The farm types identified by this study can be a good starting point for guiding such future efforts.